Dielectric impact on exciton binding energy and quasiparticle bandgap in monolayer WS2 and WSe2. (6th March 2019) - Hsu, Wei-Ting; Quan, Jiamin; Wang, Chun-Yuan; Lu, Li-Syuan; Campbell, Marshall; Chang, Wen-Hao; Li, Lain-Jong; Li, Xiaoqin; Shih, Chih-Kang
Abstract: Excitons, bound electron–hole pairs in a 2D plane, dominate the optical properties of monolayer transition metal dichalcogenides (TMDs). A large exciton binding energy on the order of 0.5 eV was theoretically predicted and experimentally determined recently. These ultrastable excitons thus open an avenue to explore the exciton physics such as Bose–Einstein condensation and superfluidity at room temperature (Kasprzak et al 2006 Nature 443 409; Plumhof et al 2014 Nat. Mater . 13 247; Fogler et al 2014 Nat. Commun . 5 4555; Jiang and John 2014 Sci. Rep . 4 7432). Recent experiments further demonstrated the concept of Coulomb engineering via dielectric environments based on either solutions or few-layer graphene. However, the conducting nature of these dielectrics can lead to quenching of optical transitions. Thus, in order to utilize 'dielectric tuning' of the exciton binding energy and quasiparticle band gaps, one must use insulating dielectrics. Here, we investigate the impact of insulating dielectric environments on the exciton binding energy of monolayer WS2 and WSe2 by exciton Rydberg spectroscopy, in which the dielectric environment is systematically varied from κ   =  1.49 to 3.82. We found that, with increasing κ value, the exciton binding energy and quasiparticle bandgap exhibit significant reductions. Quantitatively, our result follows the prediction of nonlocally-screened Keldysh potential very well. The fitted 2D polarizability, , agrees rather well with previous density function theory calculations. Their close agreement validates the nonlocally screened Keldysh model which can be used to quantitatively predict the exciton binding energy for monolayer TMDs (and possibly other 2D materials) in different dielectric environments. Such a predictive model will play an important role for the design of van der Waals heterostructures and TMD-based optoelectronic devices.